Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

AutumnE

  • 3 years ago

Solve the equation: x2 - 12x = -36

  • This Question is Closed
  1. Mimi_x3
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    \[x^2-12x+36\] \(a=1,b=-12,c=36\) then use the quadratic formula \[x=\frac{-(b)\pm\sqrt{(b)^{2}-4(a)(c)}}{2a} \]

  2. Mimi_x3
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    \(x^2-12x+36=0\)*

  3. Outkast3r09
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    it's factorable -6,-6 =P

  4. apoorvk
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 3

    Why can;t we just factor this by the way?? :o \(x^2 - 6x - 6x +36\) \(=x(x-6)-6(x-6)\) \(=(x-6)^2\)

  5. Mimi_x3
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    yeah lol. \(x^2-12x=-36\) => \(x^2-12x+36\) \(a+b= -6+-6\) \(a*b=6*6\) you can justuse the quadratic formula anyway; its faster.

  6. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy